Association of Baseline Urinary Metabolic Biomarkers with ADPKD Severity in TAME-PKD Clinical Trial Participants. Issue 5 (27th May 2021) - Hallows, Kenneth R.; Althouse, Andrew D.; Li, Hui; Saitta, Biagio; Abebe, Kaleab Z.; Bae, Kyongtae T.; Miskulin, Dana C.; Perrone, Ronald D.; Seliger, Stephen L.; Watnick, Terry J.
Visual Abstract: Abstract : Key Points: Urine excretion of two key glycolytic enzymes correlated with autosomal dominant polycystic kidney disease (ADPKD) severity (height-adjusted total kidney volume and eGFR) at baseline in the TAME-PKD study population. These findings are the first to provide evidence in human urine samples that upregulated glycolytic flux is a feature of ADPKD severity. Future analyses will test whether metformin affects ADPKD disease progression and urinary metabolic biomarkers in patients during the study. Background: Recent work suggests that dysregulated cellular metabolism may play a key role in the pathogenesis of autosomal dominant polycystic kidney disease (ADPKD). The TAME-PKD clinical trial is testing the safety, tolerability, and efficacy of metformin, a regulator of cell metabolism, in patients with ADPKD. This study investigates the cross-sectional association of urinary metabolic biomarkers with ADPKD severity among TAME-PKD trial participants at baseline. Methods: Concentrations of total protein, targeted metabolites (lactate, pyruvate, succinate, and cAMP), and key glycolytic enzymes (pyruvate kinase M2 [PKM2], lactate dehydrogenase A [LDHA], and pyruvate dehydrogenase kinase 1 [PDK1]) were measured by ELISA, enzymatic assays, and immunoblotting in baseline urine specimens of 95 TAME-PKD participants. These analytes, normalized by urinary creatinine or osmolality to estimate excretion, were correlated with patients' baseline height-adjusted total kidney volumes (htTKVs) by MRI and eGFR. Additional analyses were performed, adjusting for participants' age and sex, using multivariable linear regression. Results: Greater htTKV correlated with lower eGFR ( r =−0.39; P =0.0001). Urinary protein excretion modestly correlated with eGFR (negatively) and htTKV (positively). Urinary cAMP normalized to creatinine positively correlated with eGFR. Among glycolytic enzymes, PKM2 and LDHA excretion positively correlated with htTKV, whereas PKM2 excretion negatively correlated with eGFR. These associations remained significant after adjustments for age and sex. Moreover, in adjusted models, succinate excretion was positively associated with eGFR, and protein excretion was more strongly associated with both eGFR and htTKV in patients <43 years old. Conclusions: Proteinuria correlated with ADPKD severity, and urinary excretion of PKM2 and LDHA correlated with ADPKD severity at baseline in the TAME-PKD study population. These findings are the first to provide evidence in human urine samples that upregulated glycolytic flux is a feature of ADPKD severity. Future analysis may reveal if metformin treatment affects both disease progression and the various urinary metabolic biomarkers in patients throughout the study.